What Is New in Endometrial Cancer?: Best Articles From the Past Year. Issue 4 (October 2016) - Wright, Jason D.
Abstract : This month we focus on current research in endometrial cancer. Dr. Wright discusses four recent publications, which are concluded with a "bottom line" that is the take-home message. The complete reference for each can be found inBox 1 on this page, along with direct links to the abstracts.